2017
DOI: 10.1007/s10549-017-4287-4
|View full text |Cite
|
Sign up to set email alerts
|

Limited influence of germline genetic variation on all-cause mortality in women with early onset breast cancer: evidence from gene-based tests, single-marker regression, and whole-genome prediction

Abstract: Purpose Women diagnosed with breast cancer have heterogeneous survival outcomes that cannot be fully explained by known prognostic factors, and germline variation is a plausible but unconfirmed risk factor for poor survival outcomes. Methods We used three approaches to test the hypothesis that germline variation drives some differences in survival: mortality loci identification, tumor aggressiveness loci identification, and whole-genome prediction. The 2954 study participants were women diagnosed with breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In 2017, Bryan et al proved that no germline mutations were associated with the mortality rate and aggressive nature of EOBC [ 30 ], directing later research towards somatic and transcriptomic variations. Using The Cancer Genome Atlas (TCGA) and Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) databases, young age estrogen receptor-positive breast cancer patients (≤45 years) showed high mutational rate in CDH1 gene in comparison to older age patients (≥55 years) (14.5% vs. 2.9%).…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…In 2017, Bryan et al proved that no germline mutations were associated with the mortality rate and aggressive nature of EOBC [ 30 ], directing later research towards somatic and transcriptomic variations. Using The Cancer Genome Atlas (TCGA) and Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) databases, young age estrogen receptor-positive breast cancer patients (≤45 years) showed high mutational rate in CDH1 gene in comparison to older age patients (≥55 years) (14.5% vs. 2.9%).…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…Less than 10% of breast cancer incidence among young women is attributable to heritable mutations in the BRCA1 or BRCA2 genes. Further, Bryan et al (2017) found no evidence that germline mutations are related to mortality or tumour aggressiveness among breast cancer patients under age 50 [21]. Neither the incidence nor worse outcomes seen in young breast cancer patients can be entirely explained by inherited mutations.…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…All three are expressed in normal breast tissue, and FGFR2 and NEK10 are reported as under-expressed in breast tumors when compared to normal breast tissue. Additionally, NEK10 is part of a gene-rich region on chromosome 3 that also includes SLC4A7 , which has previously been implicated in breast cancer risk,(7,35) and, as our recent work suggests, may be related to progesterone receptor status of the tumor,(36) suggesting that future research in the NEK10 region may further elucidate the mechanisms of breast cancer initiation.…”
Section: Discussionmentioning
confidence: 85%